(untitled) ("Conference on Universal Science Research 2023", 2023)
The English language has a unique characteristic in the way it forms, words and constructs sentences. Wordformation is the process of creating new words from the material available in the language after certain structural and semantic formulas and patterns. Present-day English has some processes of word formation. Language is a dynamic system that evolves over time, and one of the key aspects of its evolution is the formation of new words. While primary word formation involves creating words from scratch, secondary word formation focuses on modifying or expanding existing words. Through processes such as conversion, derivation, compounding, and blending, secondary word formation adds richness and versatility to our language. In this article, we will delve into the intriguing realm of secondary ways of word formation.